Expanding Geoethics: Interrelations with Geoenvironmental Education and Sense of Place - Koupatsiaris, Alexandros Aristotelis; Hara Drinia (Sustainability, 2024)
{Human existence and progress hinge on sustainability and resilience, especially in the Anthropocene Era, where the diversity of nature plays a critical role. Central to this endeavor is the realm of geoethics, which not only reshapes the role of geosciences but also fosters the development of ethical behavior and practices in our interaction with the Earth. This paper presents a conceptual framework that integrates the seemingly disparate domains of geoethics, geoenvironmental education, and the sense of place. By conducting a systematic review using the keywords “Geoethics AND Education” and “Geoethics AND place” across global databases, including Scopus, Web of Science, ProQuest, and JSTOR, up to October 2023, we seek to uncover evidence illuminating the potential connections between these concepts. Out of n = 98 records identified